Effect of polypropylene fiber on properties of modified magnesium-coal-based solid waste backfill materials. (2nd January 2023) - He, Wei; Liu, Lang; Fang, Zhiyu; Gao, Yuheng; Sun, Weiji
Graphical abstract: Highlights: Through the analysis of slump and rheological test results, the addition of polypropylene fiber reduced the flow performance of modified magnesium-coal-based solid waste backfill materials (MPFB). Polypropylene fiber reinforced MFPB mechanical properties of late effect is remarkable, early effect is not obvious. Polypropylene fiber can effectively improve the failure mode of MFPB and enhance the toughness of filling body. The mechanical properties of polypropylene fiber reinforced MFPB were analyzed from a micro perspective. The influence of polypropylene fiber on the permeability of MFPB was discussed. Abstract: Driven by the "dual carbon" goal, modified magnesium-coal-based solid waste backfill materials (MFPB) were gradually used in backfill mining instead of traditional backfill materials. To study the effect of polypropylene (PP) fibers with different contents and lengths on the properties of MFPB, slump tests, rheological tests, uniaxial compressive strength (UCS) tests, permeability tests, and scanning electron microscopy were carried out. The results showed that with the increase in the PP fiber content and length, the flowability of the MFPB characterized by the slump and rheological parameters deteriorated, but the UCS increased significantly, and the permeability first decreased and then increased. The mutual entanglement of PP fibers was the main reason for the poor fluidity of the MFPB. The PP fibers could effectively enhance and improve the strength and toughness of the MFPB by an anchoring effect and irregularly distributed network structure. The strengthening effect mainly occurred in the medium and long term, and the early strengthening effect was not evident. After curing for 28 d, the maximum growth rate of the UCS was 62.5%. After loading failure, the MFPB containing PP fibers still had good integrity and continuity, and there was no shedding phenomenon. The network structure that formed in the early stage due to the PP fibers did not easily segregate and precipitate. The transmission channels between the PP fibers connecting holes were the main reason that the MFPB permeability first decreased and then increased. Therefore, this study can provide a reference for the application of PP fibers to MFPB. Enhancing the performance of the backfill body has important theoretical and practical significance for the development of mine backfill.